(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Tuberculosis (TB) is a major public health issue in India. Although dual infection with tuberculosis and bacteriafungi has been reported in immunocompromised patients, their co-occurrence in individuals with preserved immunity may complicate the clinical presentation, leading to inadequate treatment and unsatisfactory outcomes. In patients with pulmonary tuberculosis, the occurrence of tubercular lesions in atypical locations may further confound the clinical picture if only one of the pathogens is isolated, initially leading to a suboptimal therapeutic response. A strong index of suspicion and additional diagnostic testing may be required for diagnosis and treatment of the second infection. We report three unusual cases of concurrent tubercular and bacterial infection, of which two are pulmonary and one is extra pulmonary.